FLT3 ligand plasma levels have no impact on outcomes after allotransplant in acute leukemia. (August 2019) - Peterlin, Pierre; Gaschet, Joelle; Guillaume, Thierry; Garnier, Alice; Eveillard, Marion; Le Bourgeois, Amandine; Cherel, Michel; Debord, Camille; Le Bris, Yannick; Theisen, Olivier; Mahé, Béatrice; Dubruille, Viviane; et al.
Highlights: Only prospective series looking at FLT3L concentrations impact after allo-HSCT. Endogenous FLT3L concentration is not a prognostic marker in this setting. FLT3L concentration could be monitored only during induction of AML. Abstract: Objective: This study was designed to assess the impact on outcomes of early soluble Fms-like tyrosine kinase 3 ligand concentrations (sFLc) in patients receiving an allogeneic hematopoietic stem cell transplantation (allo-HSCT) for acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML). Methods: This was a prospective monocentric study including all allo-HSCT patients included in the previous FLAM/FLAL study (Peterlin et al., 2019). Blood samples collected before the start of conditioning then post-transplant were frozen, stored and tested by ELISA. The parameters considered were hematopoietic recoveries, Leukemia Free Survival and Overall Survival, acute and chronic GVHD, grade 3 or 4 acute and/or extensive chronic GVHD-free and relapse-free survival (GRFS). Results: Forty-one patients were included, a total of 179 samples were assayed for sFLc. There was no impact of sFLc levels (<=median vs> median) on acute and chronic GVHD incidences, LFS, OS nor GRFS. Conclusion: At variance with induction results for AML (Peterlin et al., 2019) endogenous sFLc do not appear to be a prognostic marker at the time of or after allo-HSCT. Even though the results are negatives, this is, to the best of our knowledge, the only prospective series specifically addressing the question of sFLc impact after allo-HSCT in acute leukemias.